(untitled) (Nativa, 2024)
ABSTRACT: Gold mining has been increasing in Brazil and worldwide since 2000, causing negative effects on the environment and surrounding communities due to deforestation of open mines and the degradation of soil and rivers. This activity is historically important in the northern Brazilian state of Mato Grosso, Southern Amazon, but integrated studies are lacking. The current research sought to map areas of active alluvial gold mining in this region from 2009 to 2019, relating it to fluctuations in the national gold market as a tool for inspection, prevention and mitigation of related environmental damage. The study was carried out by remote sensing with LANDSAT and IRS satellite images in six stages, ranging from the survey of gold mines found in loco to the analysis of the relationship between the evolution of exploited areas and the price of gold. Eight mining zones were identified. The exploited areas were dimensioned by year and mining zone, indicating an overall 195% growth. This growth was not homogeneous among the mining zones. The true price per gram of gold increased by 56.62% during the study period. Mining fronts have approached and/or encroached on conservation units and indigenous lands. The relationship between price variation and the area exploited was significant and positive in the eight zones (α=0.05). This was the first detailed mapping of gold mines at the regional level in eleven years to support effective public policies in overcoming persistent socio-environmental conflicts related to the activity. Keywords:Amazonian rivers from the Brazilian Shield; deforestation; conservation units; indigenous lands; small-scale mining; Tapajos basin. Onze anos monitorando a moderna corrida do ouro no sul da Amazônia RESUMO: A mineração de ouro vem aumentando no Brasil e no mundo desde 2000, causando efeitos negativos ao meio ambiente e às comunidades do entorno devido ao desmatamento para abertura de minas e à degradação do solo e dos rios. Essa atividade carrega importância histórica no norte do estado brasileiro de Mato Grosso, sul da Amazônia, mas há uma carência de estudos integrados a respeito. A presente pesquisa buscou mapear áreas de mineração de ouro aluvial ativa nessa região de 2009 a 2019 relacionando-a às flutuações do mercado nacional de ouro como ferramenta de fiscalização, prevenção e mitigação de danos ambientais relacionados. O estudo foi realizado por sensoriamento remoto com imagens de satélite LANDSAT e IRS em seis etapas, abrangendo desde o levantamento das minas de ouro encontradas in loco até a análise da relação entre a evolução das áreas exploradas e o preço do ouro. Oito zonas de mineração foram identificadas. As áreas exploradas foram dimensionadas por ano e zona de mineração e indicaram um crescimento geral de 195%. Esse crescimento não foi homogêneo entre as zonas de mineração. O preço real por grama de ouro aumentou 56,62% durante o período do estudo. Frentes de lavra mineral se aproximaram e/ou invadiram unidades de conservação e terras indígenas. A relação entre variação de preço e área explorada foi significativa e positiva nas oito zonas (α=0,05). Este foi o primeiro mapeamento detalhado de minas de ouro em onze anos em nível regional para embasar políticas públicas efetivas na superação de conflitos socioambientais persistentes relacionados à atividade. Palavras-chave: Rios Amazônicos do Escudo Brasileiro; desmatamento; unidades de conservação; terras indígenas; mineração em pequena escala; bacia do Tapajós.